2017
DOI: 10.5433/1679-0359.2017v38n3p1655
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of tambaqui broodstocks in stock enhancement programs

Abstract: Natural populations of tambaqui (Colossoma macropomum) have significantly decreased in recent decades especially due to human extraction activities. So that the environmental impact may be reduced, the restocking of fish and increase in fish production are enhanced. Genetic evaluations using molecular markers are essential for this purpose. Current study evaluates the genetic variability of two tambaqui broodstocks used in restocking programs. Sixty-five samples (33 samples from broodstock A and 32 samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The total number of alleles per locus ranged from five (Cm1C8, Cm1E3 and Cm1H8) to eight (Cm1A8), with sizes between 140 bp (Cm1A8) to 310 bp (Cm1E3). The number of alleles identified in loci Cm1A11, Cm1C8 and Cm1H8 was similar to that observed in two broodstocks investigated by Moraes et al (2017). However, the six loci presented lower numbers of alleles than those found by Santos et al (2009) in a wild population collected on the São Miguel Island, Pará, who obtained number of alleles between 7 (Cm1A8) and 21 alleles (Cm1H8) for the same loci implemented in this study.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The total number of alleles per locus ranged from five (Cm1C8, Cm1E3 and Cm1H8) to eight (Cm1A8), with sizes between 140 bp (Cm1A8) to 310 bp (Cm1E3). The number of alleles identified in loci Cm1A11, Cm1C8 and Cm1H8 was similar to that observed in two broodstocks investigated by Moraes et al (2017). However, the six loci presented lower numbers of alleles than those found by Santos et al (2009) in a wild population collected on the São Miguel Island, Pará, who obtained number of alleles between 7 (Cm1A8) and 21 alleles (Cm1H8) for the same loci implemented in this study.…”
Section: Resultssupporting
confidence: 88%
“…In a study with C. macropomum broodstocks in Brazil, Santos et al (2016) found He ranging from 0.48 to 0.63 and Ho from 0.26 to 0.52, which demonstrated a heterozygote deficit shown by the F IS . Moraes et al (2017) also found values of this coefficient from 0.229 to 0.348 in two broodstocks in the Northern region. It is expected that in stocks kept in captivity, there will be a decrease in genetic diversity as a consequence of intentional selection and of the mating among parental (Jacometo et al, 2010;Lopera-Barrero et al, 2015;Santos et al, 2016).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Tambaqui production has been increasing in Brazil over the last years and, according to Instituto Brasileiro de Geografia e Estatística [IBGE] (2018) the cultivation of this species was responsible for 19.7% of continental aquaculture production in 2018. Nevertheless, there is still a lack of information on genetic evaluation in breeding programs for tambaqui (Moraes et al, 2017). The management of genetic diversity in cultivated fish stocks of economic importance such as tambaqui is critical and can have direct implications on the quality of the products available to consumers.…”
Section: Resultsmentioning
confidence: 99%